Toward a contingent resource-based theory: the impact of information asymmetry on the value of capabilities in veterinary medicine - Brush, Thomas H.; Artz, Kendall (Strategic Management Journal, 1999)
The paper investigates the contingencies which define valuable resources in professional medical services. We identify activities with credence, experience, and search qualities in medical service industries in general, and in veterinary practices more specifically. We propose that different capabilities are needed to deliver different services and test whether the contingent combination of capabilities for particular services is linked to the performance of veterinary practices. For example, we expect that practice capabilities which help to retain clients are necessary for the successful delivery of services with experience qualities. We find evidence of performance benefits of client retention in a sample of 193 veterinary practices. We also find that in markets where competition from a new form of entrant is especially intense, an independent veterinarian’s credence activities combine with its experience and search activities to jointly improve practice profitability. Since the new entrants’ resources are mainly effective in the delivery of services with search qualities, the practice capabilities of the independent veterinarians that allow them to offer services with credence and experience qualities can be seen as a type of isolating mechanism. Copyright © 1999 John Wiley & Sons, Ltd.